From Law to Justice: Ownership Restrictions in the Fight for Agrarian Equity - Varun Chhachhar; Sumarno Sumarno; Joan Antonio Gonzales (Universitas Negeri Semarang, 2025)
This study examines the intersection of law and justice in the context of land ownership restrictions under agrarian reform in Indonesia, highlighting the tension between statutory frameworks and the pursuit of social equity. Indonesia’s Agrarian Law (Law No. 5 of 1960) and subsequent regulations were designed to redistribute land and promote equitable access, yet ownership restrictions and bureaucratic challenges often perpetuate structural inequalities, limiting the realization of true agrarian justice. This research critically analyzes the legal framework governing land tenure, including limits on private ownership, land certification, and redistribution programs, and evaluates their socio-legal implications for smallholder farmers and rural communities. The novelty of this research lies in its dual lens: it examines not only the legality of ownership restrictions but also their ethical and distributive impact, bridging legal analysis with normative considerations of justice. By situating Indonesian agrarian law within broader debates on social equity, the study identifies gaps between formal legal mechanisms and the lived realities of marginalized populations. The study contributes to both legal scholarship and policy-making by offering insights into how ownership restrictions can be reformed to better align with principles of fairness, equity, and community welfare. Ultimately, it argues that achieving agrarian justice in Indonesia requires both legal compliance and normative reforms that prioritize social justice alongside statutory regulation.